Tumor cell-selective apoptosis induction through targeting of KV10.1 via bifunctional TRAIL antibody - Pardo Luis A; Stühmer Walter; Hartung Franziska (Molecular Cancer, 2011)
Abstract Background The search for strategies to target ion channels for therapeutic applications has become of increasing interest. Especially, the potassium channel KV10.1 (Ether-á-go-go) is attractive as target since this surface protein is virtually not detected in normal tissue outside the central nervous system, but is expressed in approximately 70% of tumors from different origins. Methods We designed a single-chain antibody against an extracellular region of KV10.1 (scFv62) and fused it to the human soluble TRAIL. The KV10.1-specific scFv62 antibody -TRAIL fusion protein was expressed in CHO-K1 cells, purified by chromatography and tested for biological activity. Results Prostate cancer cells, either positive or negative for KV10.1 were treated with the purified construct. After sensitization with cytotoxic drugs, scFv62-TRAIL induced apoptosis only in KV10.1-positive cancer cells, but not in non-tumor cells, nor in tumor cells lacking KV10.1 expression. In co-cultures with KV10.1-positive cancer cells the fusion protein also induced apoptosis in bystander KV10.1-negative cancer cells, while normal prostate epithelial cells were not affected when present as bystander. Conclusions KV10.1 represents a novel therapeutic target for cancer. We could design a strategy that selectively kills tumor cells based on a KV10.1-specific antibody.